Toksisitas dan Aktivitas Anti-mikroba Ekstrak Etanol Bunga Karang dari Perairan Pulau Tabuhan Banyuwangi dan Pulau Menjangan Bali Barat - Erna Prawita Setyowati; Umar Anggara Jenie; Sudarsono Sudarsono; Broto Kardono (Universitas Gadjah Mada, 2007)
The purpose of the research were to determine the toxicity and antimicrobial activity of ethanolic extract of sponges collected from Tabuhan Island, Banyuwangi and Menjangan Island, West Bali. Extracts were made by maceration of the sponge samples for 3 x 24 hours. The toxicity test was carried out by Brine Shrimp Lethality Test (BST) with 48 hours-old Artemia sp. The effect of ethanolic extract was identified by determining the mortality of Artemia sp. and LC50 of each extract was analyzed by using probit analysis. Antimicrobial activity was tested by agar diffusion method. The result showed that several ethanolic extracts exhibited toxicity to Artemia sp. The toxicity test showed that extract of sponge code B43 was the most toxic with the LC50 of 8.4 µg/ml. Antimicrobial activity test exhibited that ethanolic extract of sponge with code numbers B2, B57, B61 dan W5 were active against Candida ablicans, while the axtracts of sponge with code numbers B9, B35, B47, B51 (Liosina sp.), B57, B61, B63 and W11 were active against Staphylococcus aureus. One ethanolic extract from sponge with code number B57 exibited activity against Eschericia coli.